Penyadapan Ditinjau Menurut Undang-Undang No. 11 Tahun 2008 dan Hukum Islam - Fitri Juwita; Dame Siregar (Jurnal El-Thawalib, 2022)
The problem in this reseach is tapping, because tapping is one of the  stealing activities with or without installing additional devices or devices on the telecommunication network to obtain information either secretly or openly. Wiretapping activities have existed since the first world war which was carried out to maintain national defense and security. Now tapping is carried out to uncover various corruption cases related out state financial losses. The purpose of this study is to determine of electronic information tapping in law number 11 of 2008 and to find out islamic law against the crime of tapping electronic information numer 11 of 2008.The research method used is a qualitative method with the type of library research, the data is mostly taken from books and journals. Including primary journals, namely law no 11 of 2008 on information and electronic transactions.The research results show that the first law on wiretapping was formed because on the basis of the 1995 constitution which states that the right to communicate must be protected, those who violate the the law will be sentenced to 10 years in prison and a maximum fine of Rp. 800,000,000.00 ( eight hundred million rupiah). Second, in the law of tajassus, the criminal act of tajassus committed by muslims against other muslims will be subject to ta`zir punishment and if is carried out by infidels harby to muslims, it will be punished by death.